Karakteristik Batuan Sumber (Source Rock) Hidrokarbon pada Formasi Batuasih di daerah Sukabumi, Jawa Barat - Praptisih, Praptisih; Kamtono, Kamtono; Putra, P. S.; Hendrizan, M. (Indonesian Journal on Geoscience, 2009)
http://dx.doi.org/10.17014/ijog.vol4no3.20092The purpose of the study carried out on the claystone of Batuasih Formation in Sukabumi area is to find out the hidrocarbon potential and its characteristics. The Batuasih Formation, overlying conform- ably the Walat Formation, consists  of claystone, dark gray, shaly, brittle, containing clay ball, calcite veins, with carbonate intercalations. The geochemical analysis conducted on twelve samples shows the TOC values vary between 0.49 – 1.14 % and Tmax of 431 – 434o C. Four samples are categorized to be immature, while the rests are mature. HI values of the Batuasih Formation varying from 77-191 mg HC/ TOC indicate that the samples are of C and CD organic facies. Based on those analyses, the source rock is favourably potential to generate a small quantity of hydrocarbon and gas. The hydrocarbon source rock potential level in the investigation area shows a poor to fair organic richness, and its kerogen is included into types II and III. The source rock quality based on the Hydrogen Index (HI) value tends to be a gas prone.